Scapular kinematics and muscle activity during Yi Jin Bang exercises - Liu, Jinde; Hui, Stanley Sai-chuen; Yang, Yijian; Liu, Yanhao; Song, Qipeng; Mao, Dewei (Frontiers in Physiology, 2023)
Introduction: Scapular dyskinesis is commonly associated with subacromial pain syndrome (SAPS). Addressing scapular dyskinesis is widely accepted as an important component of shoulder rehabilitation. Our previous randomized controlled trial showed that Yi Jin Bang (YJB) exercises could effectively manage SAPS, but scapular motions and muscle activity during YJB exercises remain unknown. This study examined scapular kinematics synchronously with scapular muscle activation during YJB exercises. Methods: Thirty healthy participants with no shoulder complaints were enrolled in this study. Three-dimensional (3D) scapular kinematics and electromyography (EMG) activation of the upper trapezius, middle trapezius, lower trapezius, serratus anterior, anterior deltoid, middle deltoid, and posterior deltoid were synchronously measured during nine YJB movements. Results: During all YJB movements, the scapula was upwardly rotated and anteriorly tilted, with more upward rotation and a similar or less anterior tilt than the mean resting scapular angle. Column rotation, arm crossover, shoulder support circle, and armpit support high lift generated more internal rotation than the mean resting scapular angle, with the angles of internal rotation significantly greater than the other five movements (p < 0.001). Regarding EMG activity, all YJB movements elicited low activity (1.42%-19.19% maximal voluntary isometric contraction [MVIC]) from the upper trapezius and posterior deltoid and low to moderate activity (0.52%-29.50% MVIC) from the middle trapezius, lower trapezius, serratus anterior, anterior deltoid, and middle deltoid. Conclusion: YJB exercises could be useful in the middle to later phases of shoulder rehabilitation. For patients with insufficient external rotation, some YJB movements should be prescribed with caution.